2015
DOI: 10.1074/jbc.m115.639534
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Pectin Methylesterification

Abstract: Background: PME and PMEI isoforms are co-expressed in Arabidopsis. Their biochemical interaction is yet to be characterized. Results:The processive activity of AtPME3 is regulated by AtPMEI7 in a pH-dependent manner in vitro. Conclusion: AtPMEI7 is a key component of the regulation of AtPME3 activity in planta. Significance: The tuning of AtPME3 activity by AtPMEI7 brings insights into the control of homogalacturonan methylesterification in plant cell walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…SALK_092577C ( gaut10–3 ) is a null allele characterized in this study. Other alleles used in this study have been previously published as null/knock-out mutants: vps35b-1 (SALK_014345) (15); bdx-2 (SALK_142260) (16); camta2 (SALK_007027) (17); gapcp2.2 (SALK_008979) (18); atrh8 (SALK_016830) (19); smp2 (SALK_127730) (20); pme17–2 (SALK_059908) (21); SALK_063023 (22); nadp-me4 (SALK_064163) (23); rhip1–1 (SALK_091518) (24); SALK_111575 (25); cka2–1 (SALK_129331) (26); SALK_145341 (27); SALK_151595 (28); and impl2–3 (SAIL_35_A08) (29). For proteomics profiling, Col-0 seeds were surfaced sterilized using 50% bleach and 0.01% Triton X-100 for 10 min and then washed five times with sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…SALK_092577C ( gaut10–3 ) is a null allele characterized in this study. Other alleles used in this study have been previously published as null/knock-out mutants: vps35b-1 (SALK_014345) (15); bdx-2 (SALK_142260) (16); camta2 (SALK_007027) (17); gapcp2.2 (SALK_008979) (18); atrh8 (SALK_016830) (19); smp2 (SALK_127730) (20); pme17–2 (SALK_059908) (21); SALK_063023 (22); nadp-me4 (SALK_064163) (23); rhip1–1 (SALK_091518) (24); SALK_111575 (25); cka2–1 (SALK_129331) (26); SALK_145341 (27); SALK_151595 (28); and impl2–3 (SAIL_35_A08) (29). For proteomics profiling, Col-0 seeds were surfaced sterilized using 50% bleach and 0.01% Triton X-100 for 10 min and then washed five times with sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…Interaction studies performed in vitro at different pH values (pH 5.5, 7.5 & 8.5; pH 7.5; pH 5.5 & 7.5; pH 6.5, 7.5 & 8.5) indicated formation of a stoichiometric 1:1 complex of PMEIs with endogenous PMEs but also with enzymes from other species [ 41 , 53 , 56 , 57 ]. For example, Jolie et al [ 58 ] showed that purified PMEI from kiwi can bind to PMEs from carrot and broccoli (at pH 6.5), whereas tomato and Arabidopsis PMEIs can interact and inhibit PMEs from orange (at pH 7.5 and pH 7, respectively) [ 30 , 59 ]. On the other hand, plant PMEIs do not seem capable of inhibiting fungal or bacterial PMEs, as was shown for PMEI1 and PMEI2 from Arabidopsis, which did not affect PME activity of Botrytis cinerea [ 26 ].…”
Section: Pme Inhibitor Structure and Interaction With Pectin Estermentioning
confidence: 99%
“…In addition, hydrolysis of partially de-methylesterified HG can lead to the formation of signaling molecules (oligogalacturonides), for instance, during plant-pathogen interactions [ 26 , 27 ]. Consequently, PME activity is tightly regulated at: (a) the transcriptional level [ 28 ], (b) by protein processing [ 1 ] and degradation [ 29 ], (c) by the pH of the cell wall environment [ 6 , 30 ], and (d) by endogenous inhibitor proteins called pectin methylesterase inhibitors (PMEI, Figure 1 ) [ 31 , 32 ]. The first PMEI was identified in kiwi fruit ( Actinidia deliciosa [ 33 ]) and to date several PMEIs have been investigated in different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overexpression of PMEI limits the movement of tobamovirus (tobacco mosaic virus) in tobacco and Arabidopsis, and reduces plant susceptibility to the virus ( Lionetti et al, 2014 ). Arabidopsis PME3 and PMEI7 were shown to have overlapping expression patterns in the etiolated hypocotyls when undergoing HGA methylesterification during plant development ( Sénéchal et al, 2015 ). Overexpression of Arabidopsis PME5 and PMEI3 resulted in softer and harder shoot apical meristem cell walls, respectively ( Peaucelle et al, 2011 ).…”
Section: Cell Wall Remodeling In Heat Responsementioning
confidence: 99%